Métodos simplificados de síntese de copolímeros através da combinação das técnicas SET-LRP e ROP - Trindade, Suelen Gauna (2017)
The present work focuses on the synthesis of diblock copolymers of the type polyester-block-poly(acrylate) by one-pot methodology, by combining the polymerization techniques ROP and SET-LRP. The proposed strategy was based on the use of a heterofunctional initiator that has functional groups capable of initiating polymerizations by both mechanisms in only two stages of synthesis, in the same reaction vessel and without the need for prior purification between stages. In the study, the effects of the presence of ROP catalyst, solvent type and monomer structure on the polymerization kinetics of the SET-LRP step and the copolymer quality were evaluated. By optimizing the synthesis conditions, copolymers with low dispersity and well controlled molar mass were obtained.